Bilateral mandibular dentigerous cyst in non-syndromic patient: technical strategy and literature review - Santos, Ana Flávia; Hadad, Henrique; Colombo, Luara Teixeira; da Silva, Rodrigo Capalbo; Poli, Pier Paolo; Garcia Junior, Idelmo Rangel; Souza, Francisley Ávila (ARCHIVES OF HEALTH INVESTIGATION, 2020)
Unilateral dentigerous cyst is a common entity in the oral cavity. Conversely, bilateral dentigerous cysts are rare, especially in non-syndromic patients. The purpose of the present article was to report a case of a bilateral dentigerous cyst in a non-syndromic patient and discuss about the treatment strategy. A literature review was perfomed and only eleven articles was report describing this condition. The orthopantomograph showed impacted wisdom teeth and a bilateral well-defined radiolucent unilocular image around the crown of the lower third molars. The diagnostic hypothesis was bilateral dentigerous cyst. The extraction of the impacted teeth was performed followed by excisional biopsy, which confirmed the diagnosis of dentigerous cyst. It might be concluded that radiographic examination is the first resource to intercept initial changes in the dental follicle through observation of the radiolucent halo. The histopathological examination of the surgical specimen becomes essential to reach a final diagnosis of the lesion. Descriptors: Dentigerous Cyst; Molar, Third; Surgery, Oral. Referências Daley TD, Wysocki GP, Pringle GA. Relative incidence of odontogenic tumors and oral and jaw cysts in a Canadian population. Oral Surg Oral Med Oral Pathol. 1994;77(3):276-80. Zhang LL, Yang R, Zhang L, Li W, MacDonald-Jankowski D, Poh CF. Dentigerous cyst: a retrospective clinicopathological analysis of 2082 dentigerous cysts in British Columbia, Canada. Int J Oral Maxillofac Surg. 2010;39(9):878-82. Farah CS, Savage NW. Pericoronal radiolucencies and the significance of early detection. Aust Dent J. 2002;47(3):262-265. Ricucci D, Mannocci F, Ford TR. A study of periapical lesions correlating the presence of a radiopaque lamina with histological findings. Oral Surg Oral Med Oral Pathol Oral Radiol Endod. 2006;101(3):389-94. Vencio EF, Mota A, de Melo Pinho C, Dias Filho AA. Odontogenic keratocyst in maxillary sinus with invasive behaviour. J Oral Pathol Med. 2006;35(4):249-51. Al-Khateeb TH, Bataineh AB. Pathology associated with impacted mandibular third molars in a group of Jordanians. J Oral Maxillofac Surg. 2006;64(11):1598-602. Motamedi MH, Talesh KT. Management of extensive dentigerous cysts. Br Dent J. 2005;198(4):203-6. Smith G. Two dentigerous cysts in the mandible of one patient. Case report. Aust Dent J. 1996;41(5):291-93. Fujii R, Kawakami M, Hyomoto M, Ishida J, Kirita T. Panoramic findings for predicting eruption of mandibular premolars associated with dentigerous cyst after marsupialization. J Oral Maxillofac Surg. 2008;66(2):272-76. Motamedi MH, Talesh KT. Management of extensive dentigerous cysts. Br Dent J. 2005;198(4):203-6. Tamgadge A, Tamgadge S, Bhatt D, Bhalerao S, Pereira T, Padhye M. Bilateral dentigerous cyst in a non-syndromic patient: Report of an unusual case with review of the literature. J Oral Maxillofac Pathol. 2011;15(1):91-5. Aher V, Chander PM, Chikkalingaiah RG, Ali FM. Dentigerous cysts in four quadrants: a rare and first reported case. J Surg Tech Case Rep. 2013;5(1):21-6. Pell GJ, Gregory GT. Impacted mandibular third molars: Classification and modified technique for removel. Dent Dig 1933; 39:330-38. Winter GB. Principles of exodontia as applied to the impacted third molar. St Louis: American Medical Books; 1926. Daley TD, Wysocki GP, Pringle GA. Relative incidence of odontogenic tumors and oral and jaw cysts in a Canadian population. Oral Surg Oral Med Oral Pathol. 1994;77(3):276-80. Shafer WG, Hine MK, Levy BM. A Textbook of Oral Pathology. 4th ed. Philadelphia: Saunders; 1983. 258-317 Khandeparker RV, Khandeparker PV, Virginkar A, et al. Bilateral Maxillary Dentigerous Cysts in a Nonsyndromic Child: A Rare Presentation and Review of the Literature. Case Rep Dent 2018; 2018:7583082. Imada TSN, Tieghi Neto V, Bernini GF, Silva Santos PS, Rubira-Bullen IR, Bravo-Calderón D et al. Unusual bilateral dentigerous cysts in a nonsyndromic patient assessed by cone beam computed tomography. Contemp Clin Dent. 2014;5(2):240-42. Sanjay CJ, David CM, Kaul R, Shilpa PS. Kissing dentigerous cysts involving mandibular canines: report of unusual case with review of literature. J Calif Dent Assoc. 2015;43(1):29-33. Byatnal A, Byatnal A, Singh A, Narayanaswamy V, Radhakrishnan R. Bilateral impacted inverted mesiodens associated with dentigerous cyst. J Calif Dent Assoc. 2013;41(10):753-57. Ishihara Y, Kamioka H, Takano-Yamamoto T, Yamashiro T. Patient with nonsyndromic bilateral and multiple impacted teeth and dentigerous cysts. Am J Orthod Dentofacial Orthop. 2012;141(2):228-241. Shirazian S, Agha-Hosseini F. Non-syndromic bilateral dentigerous cysts associated with permanent second premolars. Clin Pract. 2011;1(3):e64. Prasad LK, Chakravarthi PS, Sridhar M, Ramakumar Y, Kattimani V. Nonsyndromic Bilateral Maxillary and Unilateral Mandibular Multiple Dentigerous Cysts in a Young Girl: Report of a Rare Case. Int J Clin Pediatr Dent. 2010;3(3):219-23. Saluja JS, Ramakrishnan MJ, Vinit GB, Jaiswara C. Multiple dentigerous cysts in a nonsyndromic minor patient: Report of an unusual case. Natl J Maxillofac Surg. 2010;1(2):168-72. Cury SEV, Cury MDPN, Cury SEN, Pontes FSC, Pontes HAR, Rodini C et al. Bilateral dentigerous cyst in a nonsyndromic patient: case report and literature review. J Dent Child (Chic). 2009;76(1):92-6. Ustuner E, Fitoz S, Atasoy C, Erden I, Akyar S. Bilateral maxillary dentigerous cysts: a case report. Oral Surg Oral Med Oral Pathol Oral Radiol Endod. 2003;95(5):632-35. Ko KS, Dover DG, Jordan RC. Bilateral dentigerous cysts--report of an unusual case and review of the literature. J Can Dent Assoc. 1999;65(1):49-51. Chew YS, Aghabeigi B. Spontaneous regression of bilateral dentigerous cysts: a case report. Dent Update. 2008;35(1):63-5. Shah N, Thuau H, Beale I. Spontaneous regression of bilateral dentigerous cysts associated with impacted mandibular third molars. Br Dent J. 2002;192(2):75-6. Aggarwal P, Saxena S. Aggressive growth and neoplastic potential of dentigerous cysts with particular reference to central mucoepidermoid carcinoma. Br J Oral Maxillofac Surg. 2011;49(6):e36-9. Zapała-Pośpiech A, Wyszyńska-Pawelec G, Adamek D, Tomaszewska R, Zaleska M, Zapała J. Malignant transformation in the course of a dentigerous cyst: a problem for a clinician and a pathologist. Considerations based on a case report. Pol J Pathol. 2013;64(1):64-8. Spoorthi BR, Rao RS, Rajashekaraiah PB, Patil S, Venktesaiah SS, Purushothama P. Predominantly cystic central mucoepidermoid carcinoma developing from a previously diagnosed dentigerous cyst: case report and review of the literature. Clin Pract. 2013;3(2):e19. Bereket C, Bekçioğlu B, Koyuncu M, Şener İ, Kandemir B, Türer A. Intraosseous carcinoma arising from an odontogenic cyst: a case report. Oral Surg Oral Med Oral Pathol Oral Radiol. 2013;116(6):e445-49.